2020
DOI: 10.20524/aog.2020.0481
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of new direct-acting antivirals in kidney transplant recipients with chronic hepatitis C: a single-center study

Abstract: Background The recent interferon-free direct-acting antiviral (DAA) regimens have very good safety and efficacy profiles and are highly recommended for kidney transplant (KT) recipients with chronic hepatitis C (CHC). Methods All KT recipients with CHC followed at our hospital and who received therapy with the current DAAs were included. At the baseline visit, demographic, clinical and laboratory variables before and after KT, as well as at the commencement of DAAs, at the end of antiviral therapy and the end … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Early in DAAs era, SOF was not recommended in patients with eGFR < 30 mL/min due to possible accumulation of SOF and its metabolites causing renal dysfunction[ 71 ]. However, various studies have reported favorable response of SOF with RBV in RTRs[ 149 , 150 ]. We have observed 89.2% end-of-treatment response (ETR) and 100% SVR12 in our renal transplant population treated exclusively with SOF and RBV combination.…”
Section: Renal Transplant Recipientsmentioning
confidence: 99%
“…Early in DAAs era, SOF was not recommended in patients with eGFR < 30 mL/min due to possible accumulation of SOF and its metabolites causing renal dysfunction[ 71 ]. However, various studies have reported favorable response of SOF with RBV in RTRs[ 149 , 150 ]. We have observed 89.2% end-of-treatment response (ETR) and 100% SVR12 in our renal transplant population treated exclusively with SOF and RBV combination.…”
Section: Renal Transplant Recipientsmentioning
confidence: 99%
“…Moreover, those patients recovering from treatment still remained the risk of reinfection. Despite effective direct-acting antiviral drugs (DAA) were introduced, there were still strong recommendations for preventive HCV vaccination ( Darema et al, 2020 ; Martinello et al, 2020 ). Among the 73 HCV patients, the expression level of IL-35 in serum was observed to elevate in HCV patients.…”
Section: The Roles Of Interleukin-35 In Liver Diseasesmentioning
confidence: 99%